2023
DOI: 10.1002/adma.202211866
|View full text |Cite
|
Sign up to set email alerts
|

Selective Methionine Pool Exhaustion Mediated by a Sequential Positioned MOF Nanotransformer for Intense Cancer Immunotherapy

Abstract: Cancer cells are addictive to exogenous methionine to gear toward tumor proliferation. Meanwhile, they can replenish methionine pool from polyamine metabolism through a methionine salvage pathway. However, the current developed therapeutic tactics for methionine depletion are still facing great challenges in terms of the selectivity, safety, and efficiency. Herein, a sequential positioned metal-organic framework (MOF) nanotransformer is designed to selectively exhaust the methionine pool via inhibiting the upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Immunotherapy aims to enhance antitumor responses by engaging both innate and adaptive immune systems through strategies such as administering immune checkpoint inhibitors like anti-PD-1 or anti-PD-L1 antibodies. Nevertheless, practical applications of immunotherapy often encounter challenges including low efficacy in inducing immune responses and potential effects related to immunity regulation. , Fortunately, nanozymes with intrinsic enzyme-like activity have emerged as promising agents capable of reversing the immunosuppressive microenvironment in vivo , thereby addressing the limitations associated with conventional immunotherapy . For example, Zhang et al reported a Co,N-doped carbon dot exhibiting POD-like activity capable of catalyzing H 2 O 2 to generate ROS and induce DNA damage .…”
Section: Application Of Nanozymes In Enhancing Anticancer Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapy aims to enhance antitumor responses by engaging both innate and adaptive immune systems through strategies such as administering immune checkpoint inhibitors like anti-PD-1 or anti-PD-L1 antibodies. Nevertheless, practical applications of immunotherapy often encounter challenges including low efficacy in inducing immune responses and potential effects related to immunity regulation. , Fortunately, nanozymes with intrinsic enzyme-like activity have emerged as promising agents capable of reversing the immunosuppressive microenvironment in vivo , thereby addressing the limitations associated with conventional immunotherapy . For example, Zhang et al reported a Co,N-doped carbon dot exhibiting POD-like activity capable of catalyzing H 2 O 2 to generate ROS and induce DNA damage .…”
Section: Application Of Nanozymes In Enhancing Anticancer Effectsmentioning
confidence: 99%
“…Nevertheless, practical applications of immunotherapy often encounter challenges including low efficacy in inducing immune responses and potential effects related to immunity regulation. 237,238 Fortunately, nanozymes with intrinsic enzyme-like activity have emerged as promising agents capable of reversing the immunosuppressive microenvironment in vivo, thereby addressing the limitations associated with conventional immunotherapy. 239 For example, 240 The resulting DNA damage triggered cGAS-mediated production of 2′,3′-cGAMP, which subsequently activated STING, thereby achieving immune modulation within the tumor microenvironment.…”
Section: Chemodynamic Therapymentioning
confidence: 99%
“…Although surgery, radiation therapy, and chemotherapy have gained substantial application, patients still suffer from life quality deterioration, strong side effects, and chemoresistance-induced relapse as well as metastatic risks. In the past few years, immunotherapy exhibited prominent therapeutic effects in eliciting durable antitumor response and lengthening the surveillance of cancer patients, opening up a new chapter in cancer therapy. Despite its potency, the therapeutic outcome is still unsatisfactory among TNBC patients due to the “cold” tumor microenvironment. Transforming “cold” tumors into “hot” ones through improving the immunogenicity as well as promoting infiltration or activation of immune cells can significantly increase response rates of TNBC immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) composed of organic ligands and metals have been widely used in food safety detection, biomedicine, environmental remediation and monitoring, and have become a booming research trend. Compared with single-metal MOFs, bimetallic MOFs exhibited synergistic effects and enhanced properties, with more active sites, which can improve the stability of the MOF skeleton and be used as an envelope framework for biomacromolecules and a small-molecule support carrier. However, most common bimetallic MOFs had poor dispersion and low stability, which made them unable to have good colloidal properties, resulting in poor sensitivity for LFIA.…”
mentioning
confidence: 99%